PEMBELAJARAN IPAS BERBASIS KEARIFAN LOKAL KENDUREN UNTUK PENGUATAN NILAI GOTONG ROYONG DAN SOPAN SANTUN SISWA SEKOLAH DASAR - Nissa Nafida Alma; Via Widyawati; Nadiya Fika Putri Khairunnisa; Muhammad Imaduddin; Arif Mahya Fanny (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of IPAS (Natural and Social Sciences) instruction based on the Kenduren local wisdom tradition to strengthen the values ​​of gotong royong (mutual cooperation) and politeness among fourth-grade students at SDN Karangsono, as well as to identify teacher strategies and analyze obstacles encountered during the learning process. The Kenduren tradition was selected because it embodies values ​​of togetherness and etiquette that resonate with the students' lives. A qualitative case study approach was employed, utilizing structured interviews and observations. The findings indicate that the values ​​of mutual cooperation and politeness inherent in the Kenduren tradition are relevant for integration into IPAS instruction. Mutual cooperation is instilled through group discussions, peer tutoring, and the habit of helping one another, while politeness is fostered through teacher role modeling, the use of polite language, showing respect to teachers and peers, and introducing the etiquette associated with the Kenduren tradition. Implementing instruction based on local wisdom has positively impacted student behavior, evidenced by increased willingness to help peers, improved cooperation skills, the use of more polite language, and respectful attitudes toward teachers and elders. However, the study also identified a gap between understanding and application; while students can articulate these values, they do not yet consistently practice them in their daily lives, particularly outside of teacher supervision. To address this, teachers employ strategies such as peer tutoring and role modeling during morning routines, and utilize digital media such as Smart TVs to boost learning motivation. The study concludes that IPAS instruction based on the Kenduren local wisdom tradition contributes to strengthening the values ​​of mutual cooperation and politeness. Sustaining the reinforcement of these values ​​requires closer collaboration among schools, families, and the community to ensure consistent internalization in daily life.